Calcium Entry through Cyclic Nucleotide-Gated Channels in Individual Cilia of Olfactory Receptor Cells: Spatiotemporal Dynamics - Leinders-Zufall, Trese (J Neurosci, 1997)
Transient elevations of intracellular Ca(2+) play an important role in regulating the sensitivity of olfactory transduction, but such elevations have not been demonstrated in the olfactory cilia, which are the site of primary odor transduction. To begin to understand Ca(2+) signaling in olfactory cilia, we used high-resolution imaging techniques to study the Ca(2+) transients that occur in salamander olfactory receptor neurons (ORNs) as a result of cyclic nucleotide-gated (CNG) channel activation. To visualize ciliary Ca(2+) signals, we loaded ORNs with the Ca(2+)indicator dye Fluo-3 AM and measured fluorescence with a laser scanning confocal microscope. Application of the phosphodiesterase inhibitor IBMX increased fluorescence in the cilia and other neuronal compartments; the ciliary signal occurred first and was more transient. This signal could be abolished by lowering external Ca(2+) or by applying LY83583, a potent blocker of CNG channels, indicating that Ca(2+) entry through CNG channels was the primary source of fluorescence increases. Direct activation of CNG channels with low levels of 8-Br-cGMP (1 μm) led to tonic Ca(2+)signals that were restricted locally to the cilia and the dendritic knob. Elevated external K(+), which depolarizes cell membranes, increased fluorescence signals in the cell body and dendrite but failed to increase ciliary Ca(2+) fluorescence. The results demonstrate the existence and spatiotemporal properties of Ca(2+) transients in individual olfactory cilia and implicate CNG channels as a major pathway for Ca(2+) entry into ORN cilia during odor transduction.